Penyuluhan Perkembangan Inovatif Telekomunikasi di Desa Padang Padang Ulak Tanjung - Askani, Askani; Alfatah, Dhika; Purwanti, Tri; Kasdi, By; Rahayu, Novi (STIA Bengkulu, 2022)
The development of telecommunications technology in the world occurs very rapidly due to the need for to communicate and exchange data quickly, easily and mobile. Science Development about Innovative Telecommunications that exist not only develop in quality and competitiveness. In use Modern technology that exists today. With the aim of producing a society with high potential in science Knowledge of Innovative Telecommunication that has competitiveness and improves the ability of Science Telecommunication Innovative through the development of Leading Commodities from the Telecommunication Innovative Materials.Strategies that will be carried out in introducing Knowledge About Innovative Telecommunications in Padang Village Ulak Tanjung, Talang Empat District, Central Bengkulu Regency.